An Analysis of Semantic Waves: Maton’s Legitimation Code Theory for Cumulative Knowledge-Building - Ramadhan, Yolanda (Universitas Lancang Kuning, 2019)
This paper aims to state that knowledge blindness in educational research has severe obstacles to understanding knowledge development. Karl Maton offers sociological concepts of Legitimation Code Theory (LCT) - 'semantic gravity' and 'semantic density' – systematically. These concepts are used to analyse the way the classroom practices of secondary school learning in Indonesia, especially in Biology and History subjects. The researcher shows that the 'semantic wave' class can be a cumulative class practice. The most significant human society in education has the desire to build cumulative knowledge. Researchers usually produce ideas that have usefulness or attraction beyond the specificity of their original context. This research is useful to make the power to explore more in-depth knowledge with several policies that state that education must prepare students to live and work in a rapidly changing society by providing knowledge and skills that can develop throughout 'lifelong learning'. Educational learning can also be observed not only by context, but meaning and purpose also affect the cumulative and segmental parts. This problem forms the starting point for interdisciplinary research discussed in the papers collected in this special edition. Freebody (2013). At this point, the problem is the range with each discipline as the background of this research.